Programmed death-ligand 1 expression analysis for non-small cell lung cancer in tissues sampled using different methods - Ürer, Halide Nur; Günlüoğlu, Mehmet Zeki; Cansever, Levent; Bedirhan, Mehmet Ali (Galenos Yayıncılık, 2020)
Aim: This study aims at investigating the concordance of programmed death-ligand 1 (PD-L1) expression in non-small cell cancer tissues that have been sampled using different methods and its relationship with the pathologic parameters of tumors. Methods: PD-L1 expression assays were made on the cell blocks taken using fine needle aspiration, the small tissue samples representing endoscopic biopsy and the large tissue samples representing the resected tumor taken from the tumors of 100 subjects diagnosed with non-small cell lung cancer; their percentage values were evaluated and their groups were determined based on these values. Results: The average difference in expression rates found through different sampling methods was close to 0, and the values of such differences changed mostly in a narrow range. In paired comparisons, a good level of concordance was observed between all the sampling methods. The values were 0.8865 (SE: 0.0306, CI: 0.8264-0.9466) in the comparison of tumor tissue (TT) and small biopsy (SB): 0.8637, (SE: 0.033, CI: 0.7989- 0.9285) TT to cell block (CB): 0.8916, (SE: 0.0272, CI: 0.8383- 0.9449) SB tissue to the CB. Conclusion: Therefore, it can be concluded that the PD-L1 expression does not differ between the tissues sampled through various methods in non-small cell lung cancers.

Amaç: Çalışmada amacımız farklı yöntemlerle örneklenmiş küçük hücreli dışı karsinomda programmed death-ligand 1 (PDL1) ekspresyon uyumunu ve tümör patolojik parametrelerle ilişkisini araştırmaktır. Yöntemler: Küçük hücreli dışı akciğer karsinom tanısı alan 100 olgunun tümöründen ince iğne aspirasyonu hücre bloğu, endoskopik biyopsiyi temsil eden küçük doku ve rezeksiyon tümör temsil eden büyük doku örneğinde PD-L1 ekspresyon tayini yapılıp yüzde değerleri ve buna göre grupları değerlendirildi. Bulgular: Örnekleme yöntemleri tarafından saptanmış ekspresyon oranlarının ortalama farkının 0’a yakın olduğu gibi, fark değerlerinin, büyük oranda, dar uyum içinde olduğu bulundu. İkişerli karşılaştırmalarda, tüm örnekleme yöntemleri arasında, PD-L1 ekspresyon oranı açısından iyi düzeyde uyum olduğu izlendi. Tümör dokusu-biyopsi dokusu karşılaştırmasında 0,8865 (SE: 0,0306, CI: 0,8264-0,9466), tümör dokusu-hücre bloğunda 0,8637 (SE: 0,033, CI: 0,7989-0,9285); biyopsi dokusuhücre bloğunda 0,8916 (SE: 0,0272, CI: 0,8383-0,9449) idi. Sonuç: Sonuçta akciğerin küçük hücreli dışı karsinomlarında PDL1 ekspresyonu farklı yöntemlerle örneklenmiş dokular arasında fark göstermemektedir.
Farklı yöntemlerle örneklenen akciğer küçük hücreli dışı karsinom dokularında programlı ölüm ligandı 1 ekspresyon analizi
Keywords: Non-Small Cell Carcinoma; PD-L-1; Cell Block; Different Expression; Küçük Hücreli Dışı Karsinom; PD-L1; Hücre Bloğu; Farklı Yöntemler